Effectiveness and complication rates of tension-free vaginal tape, transobturator tape, and tension-free vaginal tape-obturator in the treatment of female stress urinary incontinence in a medium- to long-term follow up. Meta-analysis of randomized controlled trials - Tan, Pan-Feng; Yang, Lu-Lu; Ou, Ru-Biao; Tang, Ping; Yang, Wen-Jun; Huang, Jie-Bin; Wei, Wei; Wei, Xing-Hua; Wang, Bin; Xie, Ke-Ji (Saudi Medical Journal, 2014)
OBJECTIVE: To evaluate the effectiveness and complications of tension-free vaginal tape (TVT), transobturator tape (TOT), and tension-free vaginal tape-obturator (TVT-O) in a medium- to long-term follow up.METHODS: We searched PubMed, EMBASE, Cochrane database, ClinicalTrials.gov, Google Scholar, and the International Continence Society (ICS) website from August to December 2012 in Guangzhou First People's Hospital, Guangzhou, China. Randomized controlled trials (RCTs) comparing the effectiveness and complications of TVT, TOT, and TVT-O were selected.RESULTS: Forty RCTs were included. The TVT and TOT had similar subjective (risk ratio [RR]: 0.99; 95% confidence interval [CI]: 0.93-1.04), and objective cure rates (RR: 0.96; 95% CI: 0.70-1.32). However, TVT had a reduced risk of groin/thigh pain (RR: 0.33; 95% CI: 0.18-0.59). The subjective (RR: 1.02; 95% CI: 0.97-1.06) and objective cure rates (RR: 1.02; 95% CI: 0.99-1.06) of TVT-O were similar to TVT, but TVT had a higher risk of bladder perforations (RR: 2.29; 95% CI: 1.18-4.45). The TVT-O and TOT had similar subjective (RR: 0.99; 95% CI: 0.93-1.06), and objective cure rates (RR: 1.01; 95% CI: 0.95-1.07). However, TVT-O had a lower risk of vaginal erosion rates (RR: 0.16; 95% CI: 0.03-0.89).CONCLUSION: The subjective and objective cure rates of stress urinary incontinence were similar among TVT, TOT, and TVT-O in a medium- to long-term follow up. The TVT had a higher risk of bladder perforation than TVT-O, and a lower risk of groin/thigh pain than TOT, and TVT-O had a lower risk of vaginal erosion rates than TOT.